Social Media and Sports Marketing as Correlate of Organizing Female Football In North-Central, Nigeria - Falaye Elijah Kayode; Abdulraheem Yunusa Owolabi; Abdulraheem Mulikat (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
This study examined social media and sports marketing as correlate of organizing female football in North-central, Nigeria. Social media and sports marketing are identified in the literature as contributing factors to development of football. Therefore, there is need for sports administrators to understand this concepts. Objective: To examine the relationship that between social media and sports marketing on organization of female football clubs. Methods: The study adopt descriptive research design of correlation type, with a sampled of 100 respondents purposively selected from three female teams within the study area. Data collected were analysed using Pearson Product Moment Correlation (PPMC). Findings: The finding revealed that a significant relationship exist between use of cell phone, online marketing and mix marketing on organization of female football teams. Conclusion: It is therefore, recommended that digitalized of sports should be adopted as marketing strategy in order to enhance effective organization of female football teams.